2014
DOI: 10.1007/s12630-014-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

An observational cohort study to assess glycosylated hemoglobin screening for elective surgical patients

Abstract: Many elective surgical patients are at risk for unrecognized postoperative hyperglycemia and associated adverse outcomes. Random blood sugar testing has limited value and HbA1c may be a more appropriate test for the preoperative assessment of diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
1
16
0
4
Order By: Relevance
“…Cette prise de position a déjà été proposée dans le Journal et se fondait sur des travaux semblables des mêmes auteurs. 15,16 L'épidémiologie de cette maladie est également favorable dans ce cas : en effet, des taux élevés d'hémoglobine A1c sont prévalents dans cette population et l'examen est un test de dépistage standard de référence (c.-à-d. l'étalon or) pour détecter le diabète sucré. En effet, l'Association canadienne du diabète soutient ce type de dépistage chez les patients courant un risque accru de diabète, même si le niveau des données probantes soutenant cette recommandation et l'ampleur de la réduction du risque ne sont pas aussi élevés qu'on pourrait le croire.…”
Section: L'initiativeunclassified
See 1 more Smart Citation
“…Cette prise de position a déjà été proposée dans le Journal et se fondait sur des travaux semblables des mêmes auteurs. 15,16 L'épidémiologie de cette maladie est également favorable dans ce cas : en effet, des taux élevés d'hémoglobine A1c sont prévalents dans cette population et l'examen est un test de dépistage standard de référence (c.-à-d. l'étalon or) pour détecter le diabète sucré. En effet, l'Association canadienne du diabète soutient ce type de dépistage chez les patients courant un risque accru de diabète, même si le niveau des données probantes soutenant cette recommandation et l'ampleur de la réduction du risque ne sont pas aussi élevés qu'on pourrait le croire.…”
Section: L'initiativeunclassified
“…This position has been proposed before in the Journal, based on similar work by the same authors. 15,16 Here, disease epidemiology is again favourable: Elevated hemoglobin A1c is prevalent in this population, and the test is a reference (i.e., gold) standard screening test for diabetes mellitus. Indeed, the Canadian Diabetes Association endorses this type of case finding in patients at increased risk of developing diabetes, even if the level of evidence supporting this recommendation and the magnitude of risk reduction are not as high as one might believe.…”
mentioning
confidence: 99%
“…8 In this issue, Koumpan et al present a prospective observational study to determine the prevalence of chronic hyperglycemia in preoperative patients without a diagnosis of diabetes, the adequacy of glycemic control in preoperative patients with diabetes, and the diagnostic operating characteristics of random blood glucose and fasting blood glucose in the identification of patients with poor glycemic control. 9 Participants were adults scheduled for assessment in the study site's preoperative clinic prior to elective surgery. An HbA1c of at least 6.5% was used to provisionally diagnose diabetes and serve as the gold standard for other measurements of glycemic control.…”
mentioning
confidence: 99%
“…Amongst the participants without diagnosed diabetes, the investigators found that ''23.2% (77/332) were at very high risk for developing diabetes (pre-diabetic), and 3.9% (13/332) had a provisional diagnosis of diabetes'' based on HbA1c values. 9 Amongst the participants with known diabetes, 55.7% (39/70) had suboptimal glycemic control as defined by an HbA1c of more than 7%. The results confirm the prevalence of undiagnosed pre-diabetes and diabetes reported in earlier perioperative studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation